Radial artery pseudoaneurysm after a glass cut injury: A rare case report (Indian Journal of Case Reports, 2026)
Pseudoaneurysm of the radial artery secondary to direct penetrating trauma, rather than iatrogenic arterial injury, is rare, with reported incidence figures of 0.048–0.05% for pseudoaneurysm following arterial cannulation; the true incidence of post-traumatic cases remains unknown due to sparse reporting. We report the case of a 22-year-old male who presented with a slowly enlarging, pulsatile swelling over the right lateral aspect of the distal forearm, 1 month after an accidental glass-cut injury sutured at a local clinic. Duplex ultrasonography confirmed a 1.5 × 0.6 cm pseudoaneurysm of the distal right radial artery. He underwent surgical exploration with resection of the pseudoaneurysm and end-toend arterial reconstruction, confirmed histopathologically. The post-operative course was uneventful, with good distal perfusion at 3 months of follow-up. This case highlights the need for a high index of suspicion for pseudoaneurysm after any forearm laceration presenting with delayed swelling, and supports early surgical repair as the treatment of choice